2021
DOI: 10.13057/asianjethnobiol/y040106
|View full text |Cite
|
Sign up to set email alerts
|

Local knowledge of plant-based nutrition sources from forgotten foods in Datengan Village, East Java, Indonesia

Abstract: Abstract. Afrianto WF, Tamnge F, Hidayatullah T, Hasanah LN. 2021. Local knowledge of plant-based nutrition sources from forgotten foods in Datengan Village, East Java, Indonesia. Asian J Ethnobiol 4: 53-64. Plant-based food has benefits for health and the environment. Finding adequate plant-based nutrition sources can be found by exploring local knowledge. Here, forgotten foods mean two definitions that (i) those foods were consumed by the community before, but over time it is forgotten in the daily diet, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
2
0
1
Order By: Relevance
“…Hal ini menyebabkan ditinggalkan dan terancam punahnya keberadaan tanaman padi lokal (Salsinha et al, 2020;Sudewi et al, 2020). Oleh karena itu, harus ada upaya yang sistematis untuk menjaga kelestarian tanaman padi lokal, antara lain melalui kegiatan konservasi sumber daya genetik (Afrianto et al, 2020;Afrianto et al, 2021).…”
Section: Pendahuluanunclassified
“…Hal ini menyebabkan ditinggalkan dan terancam punahnya keberadaan tanaman padi lokal (Salsinha et al, 2020;Sudewi et al, 2020). Oleh karena itu, harus ada upaya yang sistematis untuk menjaga kelestarian tanaman padi lokal, antara lain melalui kegiatan konservasi sumber daya genetik (Afrianto et al, 2020;Afrianto et al, 2021).…”
Section: Pendahuluanunclassified
“…This study presents general information on social relation activities, biodiversity, and the supply chain system provided by rural sites. Ethnobotanical exploration is an elementary effort to identify bioprospection and strategic steps for conservation efforts (Afrianto et al 2020;Afrianto et al 2021a;Afrianto et al 2022;Afrianto et al 2023;Metananda et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The Datengan community has a long history of entomophagy practices related to beliefs, social, and cultural values. A preceding study in Datengan Village showed that there are 27 plant-rich protein sources, two fermented foods, two mushrooms, and six by-product foods that were used as protein sources in the area [17]. The result of local knowledge of protein sources from edible insects can be integrated between ethnobotany, bioprospecting, conservation efforts, and market access for sustainable protein consumption [18].…”
Section: Introductionmentioning
confidence: 99%